2D constraint modifies packing behaviour: a halobenzene monolayer with X3 halogen-bonding motif. (18th August 2021) - Davidson, Jonathan A.; Jenkins, Stephen J.; Gorrec, Fabrice; Clarke, Stuart M.
ABSTRACT: Using a combination of X-ray diffraction and simulation techniques, we are able to identify a crystalline monolayer of 1, 3, 5-triiodotrifluorobenzene formed on graphite. The monolayer is found to exhibit an incommensurate hexagonal unit cell with a lattice parameter of 9.28(7) Å, exhibiting a trigonal arrangement of iodine atoms not found in the bulk structure. DFT simulations have been performed exhibiting close agreement with the experimental structure. Importantly these simulations can be used to compare the strength of the intermolecular interactions both with and without Van der Waals corrections. Thus it is possible to estimate that halogen bonding consists of approximately half the total interaction energy. This demonstrates that despite the presence of strong directional non-covalent bonding, dispersion interactions account for a very significant proportion of the total energy. GRAPHICAL ABSTRACT: UF0001